2017
DOI: 10.3133/sir20175122
|View full text |Cite
|
Sign up to set email alerts
|

Detection of microcystin and other cyanotoxins in lakes at Isle Royale National Park, Pictured Rocks National Lakeshore, and Sleeping Bear Dunes National Lakeshore, northern Michigan, 2012–13

Abstract: For more information on the USGS-the Federal source for science about the Earth, its natural and living resources, natural hazards, and the environment-visit https://www.usgs.gov or call 1-888-ASK-USGS.For an overview of USGS information products, including maps, imagery, and publications, visit https://store.usgs.gov.Any use of trade, firm, or product names is for descriptive purposes only and does not imply endorsement by the U.S. Government.Although this information product, for the most part, is in the pub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…The US EPA method selected six MC congeners to quantitate, but there was little explanation as to why these six were chosen. When reviewing literature in search of LC/MS/MS analyses performed with more than six MC congeners and/or nontargeted analyses throughout the US, results were limited [23,24,25,26,27,28]. Based on US studies, D-Asp 3 MC-LR, D-Asp 3 -RR, Dha 7 -RR, and HtyR are often reported at more than 20% of the total MC concentration [23,24,29,30,31].…”
Section: Introductionmentioning
confidence: 99%
“…The US EPA method selected six MC congeners to quantitate, but there was little explanation as to why these six were chosen. When reviewing literature in search of LC/MS/MS analyses performed with more than six MC congeners and/or nontargeted analyses throughout the US, results were limited [23,24,25,26,27,28]. Based on US studies, D-Asp 3 MC-LR, D-Asp 3 -RR, Dha 7 -RR, and HtyR are often reported at more than 20% of the total MC concentration [23,24,29,30,31].…”
Section: Introductionmentioning
confidence: 99%